ACCELERATE – Five years accelerating cancer drug development for children and adolescents. (May 2022) - Pearson, Andrew D.J.; Weiner, Susan L.; Adamson, Peter C.; Karres, Dominik; Reaman, Gregory; Rousseau, Raphaël; Blanc, Patricia; Norga, Koen; Skolnik, Jeffrey; Kearns, Pam; Scobie, Nicole; Barry, Elly; et al.
Abstract: Rapid evaluation and subsequent regulatory approval of new drugs are critical to improving survival and reducing long-term side-effects for children and adolescents with cancer. The international multi-stakeholder organisation ACCELERATE was created to advance the timely investigation of new anti-cancer drugs. ACCELERATE has enhanced communication and understanding between academia, industry, patient advocates and regulators. It has promoted a mechanism-of-action driven drug development approach and developed Paediatric Strategy Forums. These initiatives have facilitated prioritisation of medicinal products and a focused and sequential strategy for drug development where there are multiple potential agents. ACCELERATE has championed the early assessment of promising drugs in adolescents through their inclusion in adult early phase trials. ACCELERATE has strongly supported alignment between the European Medicines Agency and the US Food and Drug Administration and identification of unmet medical needs through multi-stakeholder collaboration. Early engagement between all stakeholders in the development of new drugs is critical. Innovative clinical trial designs are required, necessitating early discussion with sponsors and regulators. Amplifying the patient advocate voice through inclusion across the drug development continuum will lead to better, patient-centric trials. By these means, children and adolescents with cancer can maximally and rapidly benefit from innovative products to improve outcomes and reduce burdensome sequelae. Highlights: The multi-stakeholder group ACCELERATE aims to advance investigation of new drugs. ACCELERATE promotes a mechanism-of-action approach and Paediatric Strategy Forums. Early engagement of all stakeholders in the development of new drugs is critical. Identification of unmet medical needs by multi-stakeholder collaboration is vital. The patient advocate voice needs to be amplified in all areas of drug development.